2017
DOI: 10.1177/1403494817744074
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of cancer mortality in Hungary between 1984 and 2013

Abstract: This study presents the seasonality pattern of different types of cancer mortality which might be related to environmental factors (e.g. infections).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Another large clinical study including 959 307 malignant tumor deaths in Hungary between 1984 and 2013 has demonstrated that the mortality was highest in the winter. However, the amplitude was small (winter to summer ratio, 1.034) 6 . In HD patients, no significant seasonal variation has been shown 8 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Another large clinical study including 959 307 malignant tumor deaths in Hungary between 1984 and 2013 has demonstrated that the mortality was highest in the winter. However, the amplitude was small (winter to summer ratio, 1.034) 6 . In HD patients, no significant seasonal variation has been shown 8 .…”
Section: Discussionmentioning
confidence: 96%
“…Death from malignant tumor has shown little or no seasonal variation 5,6,8 . A large clinical study including over 54 million deaths in 19 countries has shown that cancer mortality presented no substantial seasonality 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies present the seasonal variation in different types of cancer mortality which might be related to season specific factors such as infections, cold, diet, and environmental pollutants. [ 17 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Cancer remains the chief and ever-expanding culprit in human mortality that prompts significant concerns in every country [ 1 ]. As the International Agency for Research on Cancer (IARC) reported, this intractable disease had been emerging in approximately 18.1 million new cases and thus leading to 9.6 million cancer deaths in 2018 [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%